Una breve presentación del profesor Paulo Bonavides en oportunidad de recibir su doctorado honoris causa de la UBA - Rabinovich-Berkman, Ricardo (2013)
In the framework of the presentation of the title of Doctor Honoris Causa by the Faculty of Law of the UBA, on October 1, 2013, in the Red Room.